The effectiveness of the Employment Equity Act (Act 55 of 1998) in the public service with reference to the Department of Agriculture 2000-2006 : a South African perspective - Moeti, Kabelo Boikutso (University of Pretoria, 2013)
Dissertation (MAdmin)--University of Pretoria, 2010.